The Psychopharmacology Algorithm Project at the Harvard South Shore Program: An update on bipolar depression. (8th November 2019) - Wang, Dana; Osser, David N.
Abstract: Background: The Psychopharmacology Algorithm Project at the Harvard South Shore Program (PAPHSS) published algorithms for bipolar depression in 1999 and 2010. Developments over the past 9 years suggest that another update is needed. Methods: The 2010 algorithm and associated references were reevaluated. A literature search was conducted on PubMed for recent studies and review articles to see what changes in the recommendations were justified. Exceptions to the main algorithm for special patient populations, including those with attention‐deficit hyperactivity disorder (ADHD), posttraumatic stress disorder (PTSD), substance use disorders, anxiety disorders, and women of childbearing potential, and those with common medical comorbidities were considered. Results: Electroconvulsive therapy (ECT) is still the first‐line option for patients in need of urgent treatment. Five medications are recommended for early usage in acute bipolar depression, singly or in combinations when monotherapy fails, the order to be determined by considerations such as side effect vulnerability and patient preference. The five are lamotrigine, lurasidone, lithium, quetiapine, and cariprazine. After trials of these, possible options include antidepressants (bupropion and selective serotonin reuptake inhibitors are preferred) or valproate (very small evidence‐base). In bipolar II depression, the support for antidepressants is a little stronger but depression with mixed features and rapid cycling would usually lead to further postponement of antidepressants. Olanzapine+fluoxetine, though Food and Drug Administration (FDA) approved for bipolar depression, is not considered until beyond this point, due to metabolic side effects. The algorithm concludes with a table of other possible treatments that have some evidence. Conclusions: This revision incorporates the latest FDA‐approved treatments (lurasidone and cariprazine) and important new studies and organizes the evidence systematically.